PENGARUH STRATEGIC SUPPLIER PARTNERSHIP DAN GREEN INNOVATION CULTURE TERHADAP COMPETITIVE ADVANTAGE PADA GLOBAL SUPPLY CHAIN : Studi Kasus Pada Kosmetik XYZ - Steffi Laurencia; Lutfi Alhazami (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This study aims to determine the influence of Strategic Supplier Partnership and Green Innovation on Competitive Advantage in XYZ cosmetics in DKI Jakarta. This study was conducted using quantitative approach with a sample of 57 respondents. The instrument used by researchers is a questionnaire. Instrument testing includes validity tests and reliability tests using SPSS analysis tool version 23. Data analysis uses descriptive analysis, while hypothesis testing uses multiple linear regression analysis. The results show that Strategic Supplier Partnership and Green Innovation have a significant effect on Competitive Advantage and Strategic Supplier Partnership and Green Innovation (together) have a significant effect on Competitive Advantage